Survivor-Centered Care in Gender-Based Violence Treatment Protocol for Healthcare Providers: A Medico-legal Review (Journal of Monno Medical College, 2023)
The gender-based violence (GBV) treatment protocol for healthcare providers (HCPs) is an essential element for building the capacity of HCPs to provide better quality care to the survivors. A protocol helps to ensure that all survivors of GBV regardless of their age, background or ethnicity receive appropriate and effective care when they enter a health facility. Concern for patient welfare extends to ensuring that patients’ dignity is respected after an assault that may leave them feeling humiliated and degraded. Additionally, medical and forensic services should be provided in a manner that minimizes the number of invasive physical examinations and interviews of the patient. Rape management is generally considered as a medical emergency and the provision of medico-legal services thus takes secondary importance to general healthcare services [such as trauma treatment, evaluation and management of pregnancy and sexually transmitted infections (STIs)]. Performing a forensic examination may be considered as a negligent practice without meeting the primary healthcare needs of the patients. Health facilities are often the first entry points for GBV survivors – so, it is crucial for HCPs to be skilled and well-equipped to manage the care to the survivors. A protocol emphasizes the importance of providing survivor-centered care with an empathetic attitude to people affected by GBV includes identifying GBV, taking medical history, maintaining privacy and confidentiality and gathering medico-legal evidence.J Monno Med Coll June 2022;8(2): 53-56